A Novel SNP in the Promoter Region of IGF1 Associated With Yunshang Black Goat Kidding Number via Promoting Transcription Activity by SP1 - Li, Kunyu; Liu, Yufang; He, Xiaoyun; Tao, Lin; Jiang, Yanting; Lan, Rong; Hong, Qionghua; Chu, Mingxing (Frontiers in Cell and Developmental Biology, 2022)
IGF1, a member of the insulin-like growth factor (IGF) superfamily, is also known as the growth-promoting factor (somatomedin C). IGF1 is involved in vertebrate growth and development, immunity, cell metabolism, reproduction, and breeding. However, there are relatively few studies on the relationship between IGF1 and goat reproduction. In this study, a new transcription factor SP1 bound to the IGF1 g. 64943050T>C promoted granulosa cell (GC) proliferation. A mutation g.64943050T>C located in the promoter region of IGF1 was identified. Association analysis revealed that the kidding number in the first and second litters and the average number of first three litters of the CC genotype (2.206 ± 0.044, 2.254 ± 0.056, and 2.251 ± 0.031) were significantly higher than those in the TC genotype (1.832 ± 0.049, 1.982 ± 0.06, and 1.921 ± 0.034) and TT genotype (1.860 ± 0.090, 1.968 ± 0.117, and 1.924 ± 0.062) (p < 0.05). The kidding number in the third litter of the CC genotype (2.355 ± 0.057) was significantly higher than that in the TT genotype (2.000 ± 0.107) (p < 0.05). Then, the function of this mutation was validated by the dual-luciferase reporter assay and EMSA. The results showed that the luciferase activity of IGF1-mutant-C was significantly higher than that of IGF1-Wild-T (p < 0.05). The EMSA also showed that the binding ability of IGF1-mutant-C was higher than that of IGF1-Wild-T (p < 0.05). Subsequently, the transcription factor SP1 was predicted to bind to the mutation of IGF1 (g.64943050T>C). Overexpression of SP1 promotes the expression of IGF1 in the primary granulosa cells (GCs). The results of the CCK-8 assay and the expression of GC proliferation factors (CDK4, cyclin D1, and cyclin D2) demonstrated that SP1 promoted GC proliferation by regulating IGF1 expression. Our results suggested that the IGF1 g.64943050T>C was significantly associated with the kidding number of Yunshang black goats, and SP1 as a transcription factor of IGF1 binding to the mutation T>C regulated the expression of IGF1. Furthermore, SP1 promoted goat GC proliferation by regulating the expression of IGF1, which provides a new insight for the goat fertility trait.